Compound-specific sulfur isotope analysis of thiadiamondoids of oils from the Smackover Formation, USA. (15th October 2015) - Gvirtzman, Zvi; Said-Ahmad, Ward; Ellis, Geoffrey S.; Hill, Ronald J.; Moldowan, J. Michael; Wei, Zhibin; Amrani, Alon
Abstract: Thiadiamondoids (TDs) are diamond-like compounds with a sulfide bond located within the cage structure. These compounds were suggested as a molecular proxy for the occurrence and extent of thermochemical sulfate reduction (TSR). Compound-specific sulfur-isotope analysis of TDs may create a multi-parameter system, based on molecular and δ 34 S values that may be sensitive over a wider range of TSR and thermal maturation stages. In this study, we analyzed a suite of 12 Upper Jurassic oil and condensate samples generated from source rocks in the Smackover Formation to perform a systematic study of the sulfur isotope distribution in thiadiamondoids (one and two cages). For comparison we measured the δ 34 S composition of benzothiophenes (BTs) and dibenzothiophenes (DBTs). We also conducted pyrolysis experiments with petroleum and model compounds to have an insight into the formation mechanisms of TDs. The δ 34 S of the TDs varied significantly (ca 30‰) between the different oils depending on the degree of TSR alteration. The results showed that within the same oil, the one-cage TDs were relatively uniform, with 34 S enriched values similar to those of the coexisting BTs. The two-cage TDs had more variable δ 34 S values that range from the δ 34 S values of BTs to those of the DBTs, but with general 34 S depletion relative to one cage TDs. Hydrous pyrolysis experiments (360 °C, 40 h) with either CaSO4 or elemental S (equivalent S molar concentrations) and adamantane as a model compound demonstrate the formation of one cage TDs in relatively low yields (<0.2%). Higher concentrations of TDs were observed in the elemental sulfur experiments, most likely because of the higher rates of reaction with adamantane under these experimental conditions. These results show that the formation of TDs is not exclusive to TSR reactions, and that they can also form by reaction with reduced S species apart from sulfate reduction, though at low yields. Oxygenated compounds, most notably 2-thiaadamantanone and phenol, were also formed during these pyrolysis experiments. This may represent the first stage in the formation of sulfurized compounds and the oxidation of organic matter under TSR conditions. Pyrolysis experiments with elemental S and a TD-enriched oil showed that the δ 34 S values of the TDs did not change, whereas the BTs did change significantly. It is therefore concluded that TDs do not exchange S atoms with coexisting inorganic reduced sulfur species. They can only change their δ 34 S values via addition of newly generated TDs that form predominantly during TSR. We therefore suggest that TDs will preserve their δ 34 S values even under high-temperature reservoir conditions and will reflect the original sulfates δ 34 S value. The combination of TDs, BTs, and DBTs δ 34 S values and concentrations allowed for a more reliable detection of the occurrence and extent of TSR than either proxy alone. It showed that except for two oils, all of the oils that were measured in this study were affected by TSR or TSR-sourced H2 S, to some degree. It is still not known if some of the oils with the lower concentrations of TDs and enriched δ 34 S values (close to sulfate minerals) were affected by TSR or by a secondary charge of 34 S-enriched H2 S.